The Relationship Between Nutritional Status and the Incidence of Pneumonia in Toddlers at RS Royal Prima - Yeni Halim; Alwan Fariz Hafdar; Ikhwanul Hakim Nasution (International Journal of Health and Pharmaceutical (IJHP), 2025)
Pneumonia is a type of infectious disease that attacks the lower part of the respiratory system and is one of the leading causes of death in children. One factor that increases the likelihood of children getting pneumonia is their nutritional status. The purpose of this study is to determine the relationship between nutritional status and the incidence of pneumonia in toddlers at RS Royal Prima Medan. The research design is Analytical Observational Quantitative with a Cross Sectional approach and uses the Chi-square statistical test. Data collection was carried out in October 2025 at the Medical Records of RS Royal Prima Medan. The total sample of this study was 167 toddlers who met the Inclusion and Exclusion criteria. The indicators used in this study were Age, Gender, and Nutritional Status. The study results show a p-value (0.020) <0.05, indicating a relationship between Age and the incidence of Pneumonia, and a p-value (0.000) <0.05, indicating a relationship between Gender and the incidence of Pneumonia. The p-value (0.016) <0.05 indicates a relationship between Nutritional Status and the occurrence of Pneumonia. The conclusion of this study is that there is a significant relationship between Age, Gender, and Nutritional Status and the occurrence of Pneumonia in toddlers at Royal Prima Hospital Medan.